2012
DOI: 10.1590/s1980-57642012dn06040005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the literature on vitamin A and memory

Abstract: BackgroundOver the last 30 years, a variety of studies reporting the effects of vitamin A on memory have been published.ObjectiveTo perform a rigorous systematic review of the literature on vitamin A and memory in order to organize evidence-based data on the subject.MethodsFour authors carried out the systematic review in accordance with strict guidelines. The terms "vitamin A" OR "retinol" OR "retinoic acid" AND "memory" OR "cognition" OR "Alzheimer" were searched in virtually all medical research databases.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Different alterations of the regional distribution of 99m Tc-HMPAO retention have been reported in depressed patients [61]. Many clinical studies showed that 13-RA causes stress manifested by somatic intracranial hypertension, cerebral infarction, cerebral or thrombotic hemorrhage [62, 63], encephalopathy [64], brain blood vessel inflammation [65], and neurodegenerative disorders [66].…”
Section: Discussionmentioning
confidence: 99%
“…Different alterations of the regional distribution of 99m Tc-HMPAO retention have been reported in depressed patients [61]. Many clinical studies showed that 13-RA causes stress manifested by somatic intracranial hypertension, cerebral infarction, cerebral or thrombotic hemorrhage [62, 63], encephalopathy [64], brain blood vessel inflammation [65], and neurodegenerative disorders [66].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a systematic review of the literature was conducted according to the guidelines set forth in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. 20 The search and review of studies, carried out from September to October 2020, was performed on the SciELO, LILACS, PubMed, and Medline databases.…”
Section: Methodsmentioning
confidence: 99%
“…Using the PICo (Population, Interest and Context) framework, 20 the following research question was defined: Can educational and cognitive interventions promote improvement in psychological well-being, mood, and QoL of older adults with MCI and those with depressive symptoms? The population refers to the mature and older adults without dementia and/or with MCI, the interest refers to the psychological well-being and QoL, and context refers to educational and cognitive intervention, including memory training and cognitive stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin A can easily enter the brain and become transformed into its bioactive forms. Retinoic acid, the active form of vitamin A, is a powerful signaling molecule in the brain [146,147]. It controls the expression of many genes and influences the growth of new neurons, the survival of existing neurons, and the ability of neurons to change and adapt [147].…”
Section: Vitamin Amentioning
confidence: 99%